2018
DOI: 10.1145/3224432
|View full text |Cite
|
Sign up to set email alerts
|

Improving 3D NAND Flash Memory Lifetime by Tolerating Early Retention Loss and Process Variation

Abstract: Compared to planar (i.e., two-dimensional) NAND flash memory, 3D NAND flash memory uses a new flash cell design, and vertically stacks dozens of silicon layers in a single chip. This allows 3D NAND flash memory to increase storage density using a much less aggressive manufacturing process technology than planar NAND flash memory. The circuit-level and structural changes in 3D NAND flash memory significantly alter how different error sources affect the reliability of the memory.In this paper, through experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 80 publications
0
23
0
Order By: Relevance
“…As such, it is critical to understand the issues with data retention in flash memory. Our recent work provides detailed experimental analysis of data retention behavior of planar and 3D MLC NAND flash memory [50,52,53,167,168]. We show, among other things, that there is a wide variation in the leakiness of different flash cells: some cells leak very fast, some cells leak very slowly.…”
Section: Dram Data Retention Issuesmentioning
confidence: 77%
See 2 more Smart Citations
“…As such, it is critical to understand the issues with data retention in flash memory. Our recent work provides detailed experimental analysis of data retention behavior of planar and 3D MLC NAND flash memory [50,52,53,167,168]. We show, among other things, that there is a wide variation in the leakiness of different flash cells: some cells leak very fast, some cells leak very slowly.…”
Section: Dram Data Retention Issuesmentioning
confidence: 77%
“…We believe that, as memory technologies scale to higher densities, other problems may start appearing (or may already be going unnoticed) that can potentially threaten the foundations of secure systems. There have been recent largescale field studies of memory errors showing that both DRAM and NAND flash memory technologies are becoming less reliable [42,50,52,53,167,168,171,172,175,176,183,196,214,[227][228][229]. As detailed experimental analyses of real DRAM and NAND flash chips show, both technologies are becoming much more vulnerable to cell-to-cell interference effects [42, 45-48, 51-53, 133, 166, 175, 176, 178, 183], data retention is becoming significantly more difficult in both technologies [42-44, 46, 50, 52, 53, 59, 113, 115-117, 160, 161, 164, 167-169, 175, 178, 183, 203], and error variation within and across chip, and across operating conditions, is increasingly prominent [42, 46, 55, 57, 125-127, 147, 151, 161].…”
Section: A Other Potential Vulnerabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al measured the RBER variation before and after performing these four operations, and they also found that the P/E cycles and retention time are the main error source for 3D NAND flash [8]. The same result can be found in [26,27,29,30]. According to the research work [32,33], we plots the RBER induced by different error sources as shown in 1.…”
Section: Motivationmentioning
confidence: 63%
“…There have been recent large-scale field studies a well as small-scale controlled studies of real memory errors on real devices and systems, showing that both DRAM and NAND flash memory technologies are becoming less reliable [82, 78, 98-100, 77, 93, 28, 27, 74, 73, 17, 25, 79, 84, 80]. As detailed experimental analyses of real DRAM and NAND flash chips show, both technologies are becoming much more vulnerable to cell-to-cell interference effects [82,55,26,22,20,17,21,81,72,23,28,27,79,80], data retention is becoming significantly more difficult in both technologies [69,47,70,49,89,31,46,75,25,18,71,17,21,19,81,48,28,27,74,73,82,79], and error variation within and across chips is increasingly prominent [70,63,30,29,17,21,64,[51]…”
Section: Other Potential Vulnerabilitiesmentioning
confidence: 99%